PEREMPUAN SEBAGAI WALI NIKAH: LARANGAN ATAU PERINGATAN - Hidayati, Nurzulia Febri (Palita: Journal of Social Religion Research, 2018)
As is believed to be down and down in the marriage contract, the concept of guardians is an inseparable part, because this is one of the requirements of the legal Islamic marriage that must be met. However, the goal orientation required by marriage guardians to shift, because the context of the growing era. Formerly the marriage guardian was formulated to protect the rights of women for the realization of a harmonious marriage but later on its development precisely the dominant marriage guardians, thus neglecting the rights, choices and interests of the bride. Stereotypes of women as weak creatures result in him always in control of a marriage guardians (father, grandfather or family). Because justification of women can not be married by itself, it is deemed not to be able to marry someone else, including marrying her daughter even if she is someone who has emotional closeness. Though one step ahead of women is not far behind with men in terms of acting skills, if it is used as female reasoning does not deserve to be a guardian then it seems not right. Indeed, the construction of such guardians needs to be reexamined whether it is an absolute prohibition or impact of a perpetual tradition.